2021
DOI: 10.1111/febs.16065
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term plasticity in the hippocampus: maintaining within and ‘tagging’ between synapses

Abstract: Synapses between neurons are malleable biochemical structures, strengthening and diminishing over time dependent on the type of information they receive. This phenomenon known as synaptic plasticity underlies learning and memory, and its different forms, Long-Term Potentiation (LTP) and Long-Term Depression (LTD) perform varied cognitive roles in reinforcement, relearning and associating memories. Moreover, both LTP and LTD can exist in an early transient form (early-LTP/LTD) or a late persistent form (late-LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 235 publications
(368 reference statements)
0
33
0
Order By: Relevance
“… 22 Based on recent studies, many brain areas, including the cortex, thalamus, hippocampus, striatum, basal ganglia, and corpus callosum could be affected by CLP. 23 , 24 , 25 Of note, the hippocampus region has a close association with cognitive impairment, 26 so the hippocampus tissue was selected for our research. As demonstrated in this study, septic rats showed significant cognitive deficits, including prolonged escape latency, increased escape passage, reduced frequency of cross to the platform, and enlarged neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Based on recent studies, many brain areas, including the cortex, thalamus, hippocampus, striatum, basal ganglia, and corpus callosum could be affected by CLP. 23 , 24 , 25 Of note, the hippocampus region has a close association with cognitive impairment, 26 so the hippocampus tissue was selected for our research. As demonstrated in this study, septic rats showed significant cognitive deficits, including prolonged escape latency, increased escape passage, reduced frequency of cross to the platform, and enlarged neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to STP, long‐term plasticity (LTP) plays an important role in memory and learning through altering the synaptic weight more persistently. [ 44 ] The STP can be transformed into LTP after continuous neuronal stimulation or repeated training. To simulate the transition process from STP to LTP, a series of presynaptic voltages with fixed pulse amplitude (−1.5 V) and duration (20 ms) were applied to the TOSTs.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have shown that chronic pain accompanied by a reduction in the hippocampal volume can significantly reduce the learning ability of the body [221,222], resulting in short-and long-term memory defects [223]. At present, the widely accepted theory for the mechanism of pain-impaired memory is the alteration of hippocampal synaptic plasticity (long-term potentiation [LTP]), which is considered the molecular mechanism underlying learning and memory [224,225] or that underlying the effects of pain on memory [117,219]. In addition, morphological and biochemical changes in the hippocampal region underlie cognitive impairment in neuropathic pain [226].…”
Section: Tnf-α/necroptosis In Pain-associated Memory Deficitsmentioning
confidence: 99%